Advances in the Treatment of Behcet's Disease - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (SPRINGER, 2021)
Purpose of Review To assess current management of Behcet's disease (BD). Controversies on therapeutic approaches to different manifestations, whether conventional immunosuppressives (IS) or biologic agents, should be chosen, and options for refractory disease are discussed. Recent Findings Glucocorticoids are still the main agents for remission-induction and azathioprine the first-line conventional IS in maintenance phase to prevent relapses of major organ involvement. Apremilast is shown to be a safe and effective option approved by the FDA for oral ulcers. Large case series confirmed the efficacy and safety of TNF alpha inhibitors and Interferon-alpha. Promising results are observed with IL-1 inhibitors, ustekinumab, secukinumab, and tocilizumab for refractory BD. Although both conventional IS and biologic agents are effectively used to suppress inflammation in BD, there is still an unmet need for clear therapeutic strategies in the management for different manifestations. Further controlled studies with new biologic agents, anticoagulants and the benefit of concomitant IS usage with biologics are needed to optimize the management of BD.
Keywords: Behcet’ s disease; Treatment; Biological agents; Conventional immunosuppressives; LONG-TERM EFFICACY; REFRACTORY NEURO-BEHCET; ANTI-TNF-ALPHA; FOLLOW-UP; INTERFERON ALPHA-2A; CYCLOSPORINE-A; DOUBLE-BLIND; OPEN-LABEL; MUCOCUTANEOUS MANIFESTATIONS; REMISSION INDUCTION